VISUAL AESTHETIC STUDY BANDUNG CREATIVE HUB AS A REPRESENTATION OF CITY IDENTITY - Putri, Alfi Istiqomah Kusuma; Safeyah, Muchlisiniyati (Border: Jurnal Arsitektur, 2020)
Observing from the concept of city identity, Bandung has an identity as a creative city. However, there are still many architectural buildings that do not reflect Bandung's identity as a creative city. Bandung Creative Hub is a center of creativity that is used by the people of Bandung City as a means to create, interact, and collaborate. As a center of creative activity for the city residents, Bandung Creative Hub has certain visual aesthetic elements that can reflect the identity of the City of Bandung as a creative city. This study examines the characteristics of the visual aesthetic elements of Bandung Creative Hub as a building that represents the identity of Bandung City as a creative city. Using a qualitative descriptive method that analyzes Bandung Creative Hub based on visual aesthetic variables, including aspects of composition, cohesiveness, balance, symmetry, proportions, scale, rhythm, contrast and harmony. Visual aesthetic aspects of the Bandung Creative Hub building have attractive characteristics as a representation of Bandung's identity as a creative city. Bandung Creative Hub is an iconic building in its area because of its more prominent characteristics compared to the surrounding buildings.